Factors Associated with Perceived Family Support among Elderly with Hypertension - Icca Presilia Anggreyanti; Joni Haryanto; Puji Astuti (Alta Dharma Publisher, 2020)
Hypertension is global disease and high incidence rate. Hypertension patients were required to monitor blood pressure regularly. The study aimed at examining factors associated with perceived family support among elderly who were living with hypertension. A cross sectional study design was applied in this study. Total of 225 samples recruited by using simple random sampling. The results showed that there were positive relationship between age, gender, education, occupation, knowledge, length of care for elderly, relations of elderly-families with family support in the elderly with hypertension (p-value<0,05). The adequate information regarding management of hypertension for family caretaker need to establish to support patients to manage blood pressure level.